On Approximation Properties of Generalized q-Bernstein Operators. (4th July 2018) - Karahan, Döne; Izgi, Aydın
ABSTRACT: In this study, we identify a generalization of q -Bernstein type operators and investigate approximation properties of a sequence of these operators . We estimate rate of approximation by modulus of continuity. We prove Voronovskaya type theorem for these operators.